MANUFAKTUR ALAT PERAGA ALIRAN FLUIDA DI DALAM PIPA MODUL TAMBAHAN - Abadi, Agus Haris (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2019)
Abstract. Fluid mechanics is one of the courses that discusses the flow of fluid in a pipe. The material in it includes knowledge of energy flow losses that occur in the piping system. This flow loss, will later show the piping system performance. In lecture material, the term flow loss is known as the Head Loss. The fluid flow props in this pipe are parallel studies with basic module research. In this study, making a more varied valve module and additional measuring devices on the Headloss visual aid in the hope of helping and making effective learning of fluid mechanics in mechanical laboratories. These modules are called additional modules.Keywords: Props, Fluid Flow in the Pipe, Head Loss, Ball velve.